The Roots of Divergence: Western Economic History in Comparative Perspective - Findlay, Ronald (American Economic Review, 1992)
Now that Japan has overtaken and surpassed in arts of manufacture, it is perhaps possible to look at familiar old problem of the rise of West in a more sober and less exclusively Eurocentric way. No longer is it possible to imagine some unique set of individual and social characteristics that gave Western society an inherent superiority over others in realm of economic organization and its associated scientific and technological base. The Protestant ethic or the spirit of rational inquiry can no longer be regarded as unique to this one civilization, not only in light of recent economic performance of East Asia but because of what is now known about its past achievements in these fields as a result of research of Joseph Needham and others. Yet fact remains that indeed dominated world since at least time of European voyages of discovery around turn of 15th century, with English Industrial Revolution of 18th century consolidating its dominance and raising it to a higher level. Recognizing early achievements of other civilizations only makes it harder to account in any satisfactory way for phenomenon. It is convenient to begin with voyages of discovery themselves. It is easy to imagine them as manifesting qualities and achievements of Renaissance, bold new ideas about nature of world and their application to nautical technology and navigation. Yet all basic inventions that they utilized were transmitted to either from China (the compass and stern-post rudder, as well as gunpowder and cannon used in their predatory engagements) or from Arabs (the form of lateen sail and knowledge of winds and currents of Indian Ocean). Can one not say, however, that only could have put it all together in mounting of such long-distance ocean voyages in 15th century? The answer of course is that Chinese did precisely mount an amazing sequence of seven great voyages, over period 1405-1433, when they sent fleets of hundreds of great junks with crews of over 30,000 at a time, to Java, Sumatra, Cambodia, Ceylon, India, Persian Gulf, Red Sea, Kenya, Somalia, Madagascar, and Mozambique. Several of Chinese ships were in excess of 1,500 tons, while largest of Vasco da Gama's ships did not exceed 300 tons. Thus, there is no question that Chinese had capability to do what Portuguese did, in opposite direction. Why didn't they? In this connection, it is necessary to consider incentives in addition to capabilities. When asked what he was looking for in India, Vasco da Gama was reputed to have answered, Christians and spices, though perhaps order should have been reversed. The spice trade, based on intense need for pepper and other spices to preserve meat in Europe, had been a lucrative one for centuries. Brought from India and islands of Indonesian archipelago by Arab and Indian ships to Red Sea and Persian Gulf, spices reached Europe through intermediaries of Egyptian Mamelukes at Cairo and Venice. It was basis for centuries of unparalleled wealth (in Europe) of great maritime republic, jealously guarded against encroachments of rival Genoa. The motives for prolonged exploration for a passage around Cape of Good Hope, instigated by Prince Henry Navigator, * Department of Economics, Columbia University, 420 W. 118th St., New York, NY 10027.